TheIndependence of the Iraqi State Council, Aspects of Independence and Future Prospects - Amin, Assist. Prof. Dr. Muhammad Salim Muhammad (Journal of Legal and Political Studies, 2019)
The Sixth’s amendment of the Iraqi Shura Council’s law no. 65 of 1979 by the law no. 71 of 2017 is the most important development the council has seen، since it has made major amendments to the law، including changing its name from The State Council of Shura to The State Council and making the council an independent unit that exercises its full power after it was part of the Ministry of Justice، which itself was part of the Executive Authority. This independence implies، most importantly، financial and administrative independence، in addition to technical independence. It guarantees freedom to the council and its members in exerting their power away from the interference of the administrative authority. The research concludes with a few suggestions; most importantly، that the Iraqi Legislature pass a new law for the Council to replace the current law، which is incompatible with the changes occurred to the council، be it in its functions، arrangements or the rights of its members، which will help reactivate the council، subjugate the Executive Authority to it، and put an end to the repeated injustices of the Executive Authority to the rights of society and individuals.
Keywords: Shura Councils law no 65 of 1979; State Council of Shura; administrative independence; administrative authority; Executive Authority